Functional Outcome of Laparoscopic Ventral Mesh Rectopexy in Internal Rectal Prolapse - Md Shahidul Islam; Nusrat Jahan; Mir Rasekh Alam Ovi; Muhammad Ali Siddiquee; Muhammed Tanvir Jalal; Shamima Nasrin (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: In recent decades, a variety of surgical techniques have been developed to restore defecatory function in individuals with Obstructive Defecation Syndrome (ODS), either transanal, perineal, or abdominal. Nevertheless, none of these has been suggested as the best surgical technique to date. One of such transabdominal techniques for pelvic anatomic repair is laparoscopic ventral mesh rectopexy (LVMR), which was initially presented by D'Hoore in 2004. A related indication for LVMR is high-grade internal rectal prolapse (IRP) and/or complex rectocele with uncontrollable ODS symptoms. Additionally, it permits rectocele, enterocele, and vault prolapse correction while maintaining the pelvic floor's neuromuscular function, which improves the functional complaints related to the IRP. Methods: The Department of Colorectal Surgery at BMU, Dhaka, undertook this prospective observational study between March 2023 and February 2024. The study comprised patients over 30 who had symptomatic internal rectal prolapse and had not responded to conservative treatment with laxatives and pelvic floor exercises. Patients with incomplete families were also disqualified. After outlining the specifics of the treatment, including its benefits and drawbacks, informed written consent was acquired. A thorough physical examination, a complete colonoscopy, and an MR defecography were performed. A pre-made SPSS data sheet was used to record the results of the surgical surgery, each operative complication, the length of the procedure, the type of mesh, any further procedures, and the postoperative recuperation. Results: LVMR was performed on 19 people in our study who had ODS as a result of IRP. 73.68% of participants were over 41, 79% were female, and 73.68% had a normal BMI. The most common symptoms were fecal incontinence (21.05%), incomplete evacuation (84.21%), straining (63.16%), and assisted evacuation (100%). 52.63% had had surgery in the past. According to results from magnetic resonance defecography (MRD), 36.84% had Grade 3 IRP and 47.37% had Grade 4 IRP. With few difficulties and no conversion to open surgery, the average operative time was 125±16.29 minutes. The long-term effectiveness of the surgery was demonstrated by the mean ODS score, which considerably (p value < 0.0001) improved from 21.0 ± 1.8 preoperatively to 15.47 ± 1.35 at 3 months and further dropped to 10.37 ± 1.61 at 6 months (p value < 0.0001). Most patients (n=12) were discharged after 3 days, reflecting a relatively short hospital stay and favorable recovery outcomes. Conclusion: For patients with ODS brought on by IRP, LVMR is a safe and efficient surgical technique. It provides good functional outcomes with few problems. However, more extensive research is required to identify the best course of treatment for IRP. J Shaheed Suhrawardy Med Coll 2024; 16(2): 79-82